Telecommunications traffic, tariffs, and costs an introduction for managers - Farr, R. E. (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
Suitable for those who wish to gain a comprehensive overview of the area, this book offers guidance on planning, ordering, managing and using telecommunications facilities.
Electronic reproduction.
Keywords: Telecommunication -- Traffic; Telecommunication -- Costs; Electronic books